Automated dispensing cabinets and the effect on omitted doses of ward stock medicines; can implementation reduce delays to first dose antimicrobials? - Emma Jeffrey; Áine Walsh; Kit Lai (Exploratory Research in Clinical and Social Pharmacy)
Omitted doses are a subset of medication administration errors which have the potential to cause severe harm. Sepsis is a clinical condition where dose omissions or delays in medicines administration can be fatal. Automated dispensing cabinets (ADCs) provide a medicines management solution which keeps track of stock in real time and can automatically generate orders, reducing the likelihood of medication stockouts. This study aims to assess the impact of ADC implementation on the rate of omitted doses due to unavailability of ward stock medicines. Secondary aims are to investigate the effect of ADCs on omitted doses of first dose antimicrobials. Due doses data was compiled from the electronic prescribing and medicines administration (EPMA) system for ten wards pre-ADC implementation between July and September 2022 and was compared with data post-ADC implementation between July and September 2023. Omitted doses were selected and filtered for those marked ‘drug not available’. Ward stock lists were used to determine which omitted doses were for medicines held as ward stock. A secondary analysis filtered this data further to isolate omitted doses of ward stock medicines which were systemically administered antimicrobials. The overall number of prescribed doses during the pre-implementation period was comparable to those in the post-implementation period. There was a total of 393 omitted doses of ward stocked medicines due to unavailability pre-ADC implementation, and 817 post-ADC implementation. This represents an omission rate due to unavailability of ward stock medicines as a percentage of all prescribed doses, of 0.08 % pre-ADC and 0.18 % post-ADC implementation. Statistical analysis showed no difference (p = 0.1655). There was also no statistical difference in omitted doses of ward stocked antimicrobials pre vs post-ADC implementation (p = 0.3363). It has been identified that a potential way to reduce rates of omitted doses is by optimising stock stored in each cabinet. This research is encouraging and may warrant further data collection once stock optimisation has occurred.